Premonsoon/Postmonsoon Bay of Bengal Tropical Cyclones Intensity: Role of Air‐Sea Coupling and Large‐Scale Background State. Issue 4 (19th February 2019) - Neetu, S.; Lengaigne, M.; Vialard, J.; Samson, G.; Masson, S.; Krishnamohan, K. S.; Suresh, I.
Abstract: The densely populated Bay of Bengal (BoB) rim witnesses the deadliest tropical cyclones (TCs) globally, before and after the summer monsoon. Previous studies indicated that enhanced salinity and reduced thermal stratification reduce cooling under BoB TCs after the monsoon, suggesting that air‐sea coupling may favor stronger TCs during that season. Using observations and simulations from a one fourth degree regional ocean‐atmosphere model, we show that BoB TCs are stronger before the monsoon due to a more favorable large‐scale background state (less vertical wind shear and higher sea surface temperature). Air‐sea coupling however alleviates this background state influence, by reducing the number of premonsoon intense TCs, because of larger cooling and reduced upward enthalpy fluxes below TCs during that season. As the impact of air‐sea interactions on BoB TCs is largest for intense TCs, it should be further investigated for Category 3 and above TCs, which are not reproduced at one fourth degree resolution. Plain language summary: Tropical cyclones that develop in the Bay of Bengal are amongst the most lethal globally, owing to the dense and vulnerable coastal population living along its rim. These cyclones mostly occur in April–May and October–December, that is, before and after the Indian summer monsoon. In this study, we show that there are more intense cyclones before than after the monsoon, because of more favorable large‐scale background conditions. We however also show that more intense interactions between the cyclone and the ocean tend to reduce risks for intense cyclones before the monsoon, hence opposing the effect of background conditions. Since air‐sea coupling clearly contributes to the Bay of Bengal cyclone intensity, in particular before the monsoon, it should be accounted for in operational forecasts. Key Points: Bay of Bengal tropical cyclones are stronger before than after the monsoon, due to more favorable large‐scale background conditions Air‐sea coupling alleviates the effect of large‐scale background conditions, by inhibiting premonsoon tropical cyclones The air‐sea coupling negative feedback on tropical cyclones is weak after the monsoon, due to a fresher, less thermally stratified BoB